Fourth Workshop on Sustainable Software for Science: Practice and Experiences (WSSSPE4). Issue 1 (15th February 2018) - Katz, Daniel S.; Niemeyer, Kyle E.; Gesing, Sandra; Hwang, Lorraine; Bangerth, Wolfgang; Hettrick, Simon; Idaszak, Ray; Salac, Jean; Chue Hong, Neil; Núñez-Corrales, Santiago; Allen, Alice; Geiger, R. Stuart; et al.
This article summarizes motivations, organization, and activities of the Fourth Workshop on Sustainable Software for Science: Practice and Experiences (WSSSPE4). The WSSSPE series promotes sustainable research software by positively impacting principles and best practices, careers, learning, and credit. This article discusses the code of conduct; the mission and vision statements that were drafted at the workshop and finalized shortly after it; the keynote and idea papers, position papers, experience papers, demos, and lightning talks presented during the workshop; and a panel discussion on best practices. The main part of the article discusses the set of working groups that formed during the meeting, along with contact information for readers who may want to join a group. Finally, it discusses a survey of the workshop attendees.